Copy-number variation of housekeeping gene rpl13a in rat strains selected for nervous system excitability - Kalendar, Ruslan; Belyayev, Alexander; Zachepilo, Tatiana; Vaido, Alexander; Maidanyuk, Dmitry; Schulman, Alan H; Dyuzhikova, Natalia (Molecular and cellular probes, 2017)
We evaluated copy number variation (CNV) for four genes in rat strains differing in nervous system excitability. rpl13a copy number is significantly reduced in hippocampus and bone marrow in rats with a high excitability threshold and stress. The observed phenomenon may be associated with a role for rpl13a in lipid metabolism.
Keywords: kortikální excitabilita; nervový systém - fyziologické jevy; DNA Copy Number Variations; Ribosomal Proteins; Cortical Excitability; Copy number variation (CNV); Nervous system excitability; variabilita počtu kopií segmentů DNA; Nervous System Physiological Phenomena; krysa rodu Rattus; Hippocampus; ribozomální proteiny; Animals; Bone marrow; zvířata; Bone Marrow; Rats; Rat; kostní dřeň; Quantitative real-time multicolor multiplex PCR (qmPCR); hipokampus